(untitled) (Research, Society and Development, 2023)
A esthetics continues to experience accelerated market growth, providing opportunities for professional activity with specialists and appropriate qualifications. Aesthetic services and therapies have grown at the same speed as technologies, the production through which they influence the demand of customers who are increasingly aware of new demands due to market trends and this scenario is increasingly necessary in aesthetic clinics and beauty salons. beauty latest features and technologies. The objective of this study is to show how a pharmacist will work in the area of aesthetic health using different techniques to meet the needs of this public. The construction of the work was accompanied by an integrative bibliographic review that includes aesthetic health, achievement and development of professionals in the pharmaceutical industry who strive for efficiency and safety in the field of activity, with the search being carried out in scientific articles, which are being researched in the databases of data Scientific Electronic Library Online (SciELO), National Library of Medicine (PubMED), Websites of the Federal Pharmacy Council (CFF) and Regional Pharmacy Councils (CRF’s), in the period from February to October 2023. Means currently available for treatment aesthetic, associated with therapeutic resources allows for more effective confidence in beauty and health care techniques that produce more effective and rewarding results over the years and mainly improving the quality of life. The aesthetic pharmaceutical professional shows his skills in carefully performing aesthetic procedures to ensure the safety and health of patients.